Integrated smart system for energy audit: methodology and application. (December 2017) - Belussi, Lorenzo; Danza, Ludovico; Salamone, Francesco; Meroni, Italo; Galli, Stefano; Svaldi, Sandra Dei
Abstract: The article describes the design and the application stage of a smart energy audit system, integrated within building, and the methodologies adopted for the detection of malfunctions of the plant. The system is set up as a "black box" consisting of a hardware aimed at logging both energy and environmental parameters and a software for the assessment of building behavior and the management of energy flows. The Energy Signature was chosen as the reference method for the evaluation of the energy performance of building. The system was tested in an existing public office building.